The Effect of Professionalism, Independence, Accountability and Time Pressure on Audit Quality With Auditor's Professional Ethics as Variables Moderating - Dian Fauziah; Yuskar Yuskar (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study aims to test and proving the effect of professionalism, independence, accountability and time pressure on audit quality with auditor professional ethics as a moderating variable at Indonesian Audit Board representatives of West Sumatra. This study uses quantitative research methods that describe a causal relationship or a causal relationship.In this study, the causal relationship between professionalism, independence, accountability and time pressure on audit quality will be investigated, moderated by the auditor's professional ethics. The population of this research are auditors who work at Indonesian Audit Board representatives of West Sumatra. The sampling technique in this study was using the Saturated Sampling technique. This study uses primary data by distributing questionnaires. Respondent in this study were 70 auditors who worked at the Indonesian Audit Board Representative for West Sumatra. The method used to analyze the data in this study is multiple linear regression analysis and moderate regression analysis using SPSS 25 software. The results of this study indicate that independence, accountability and auditor’s professional ethicts affect audit quality. Whereas profesionalism and time preasure cannot affect audit quality. The relationship between independence and accountability with audit quality can be moderated by the auditor's professional ethics, while the relationship between professionalism and time pressure and audit quality cannot be moderated by the auditor's professional ethics.